Effect of Moisture Conservation Practices and N Fertilization on Water Use Efficiency and Dry Matter Accumulation in Pearl Millet - Singh, Pratap; Verma, R.S. (Journal of Soil and Water Conservation, 2022)
A field experiment was conducted with pearl millet (Pennisetum glaucum) during the rainy seasons of 1990 and 1991 at Agra to study the. effect of tillage depths, sowing methods, and nitrogen levels on dry matter accumulation, moisture conservation and water-use efficiency. Dry matter accumulation and water use efficiency increased with increasing depths of tillage being maximum tinder deep tillage. However, the seasonal and daily consumption use decreased with increase in depth of tillage. Soil moisture extraction percentage from deeper soil layers also increased with increase in tillage depths. Ridge and furrow sowing method recorded higher values of seasonal and daily consumption use, water use efficiency, moisture content, rainfall use efficiency and dry matter accumulation than flat sowing method. Lower soil profile contribute relatively more moisture under ridge and furrow method as compared to flat sowing method. Application of N upto 120 kg/ha increased daily and seasonal consumptive use, water-use effieicnty, rainfall use-efficiency, dry matter accumulation and soil moisture extraction percentage from deeper layers.